Optimizing the Salmon Algorithm for the construction of DNA error-correcting codes - Orth, J.; Houghten, S. (2011 Symposium on Computational Intelligence in Bioinformatics and Computational Biology, 2011)
DNA error correcting codes over the edit metric can be used to correct sequencing errors. The codewords may be used as embeddable markers that allow one to track the origin of sequence data. The Salmon Algorithm is a search meta-heuristic inspired by the behaviour of salmon swimming upstream to spawn. This algorithm consists of a number of parameters, which we tune for the purpose of constructing DNA error correcting codes with a large number of codewords. Using this algorithm, several best known code sizes are improved. Construction of codes obeying biological restrictions is also discussed and the use of the Salmon Algorithm for this purpose is demonstrated.